Pengaruh Motivasi, Beban Kerja, dan Kompensasi Terhadap Kinerja Karyawan pada PT. Cahaya Karya Bersama di Mojokerto - Iis Okta Vinanda; Hartono Hartono; Kasnowo Kasnowo (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to examine the effect of motivation, workload, and compensation on employee performance at PT Cahaya Karya Bersama in Mojokerto. The research employed a quantitative approach with a causal associative design to test the relationship between variables systematically. The population consisted of 40 employees, all of whom were involved as respondents through a total sampling technique to ensure comprehensive data coverage. Data collection was conducted using questionnaires measured on a Likert scale, while data analysis applied multiple linear regression with the assistance of SPSS version 25. The findings reveal that motivation has a positive and significant impact on employee performance, indicating that employees who are motivated tend to show higher levels of achievement. Workload also demonstrates a positive and significant effect, suggesting that when managed appropriately, workload can encourage employees to maximize their potential. However, the study also emphasizes the need for proportional workload management, as excessive demands may lead to stress and reduced performance in the long term. Among the three variables tested, compensation emerged as the most dominant factor influencing performance. Both financial rewards, such as salaries and allowances, and non-financial rewards, such as recognition and career development opportunities, were shown to significantly enhance employee effectiveness and productivity. Simultaneously, motivation, workload, and compensation collectively have a significant effect on employee performance, with a coefficient of determination (R²) of 0.564. This means that 56.4% of the variation in employee performance can be explained by the research model, while the remaining 43.6% is influenced by other factors outside the scope of this study. These findings highlight the strategic importance of maintaining employee motivation, managing workloads proportionally, and designing a fair compensation system. Implementing these elements effectively is expected to not only improve employee performance but also strengthen organizational competitiveness in a dynamic business environment.